Analysis of the Dynamic Service Flow Management Transactions Protocol for MAC IEEE 802.16. An Aproach - Morales Bezeira, Ana (2017)
In this work the WiMax MAC Protocol for Dynamic Service Flow management and their transactions is analyzed by showing this several pitfalls of the specification and how this can affect the implementation of the protocol using Colored Petri Nets (CPNs). A detailed description of the protocol is developed at level of transactions it supports, and at level of service flows. The modeling and analysis of the protocol are important to improve the current specification and to support the reuse of the concepts in emerging networks. We show the potentialities of using a transaction oriented approach in the description of this kind of protocols. The contributions of this paper are focused on providing a clear description of the protocol, presentation of the model, validation and analysis of the model according to the generation of the Dynamic Service Flow management transactions protocol language, as well as the determination of regular expressions Language.